Effect of desensitizing dentifrices on eroded dentin wettability - Castelo, Raisa; Arnez, Mayara Manfrin; Curylofo-Zotti, Fabiana Almeida; Corona, Silmara Aparecida Milori; Dotta, Tatiane Cristina; Almeida, Leonardo de Pádua Andrade; Ramos, Ana Paula; Catirse, Alma Blásida Concepcion Elizaur Benitez (Brazilian Dental Science, 2022)
Objective: To analyze the wettability on the surface of eroded dentin in teeth submitted to abrasive wear withdesensitizing dentifrices. Material and Methods: Bovine dentin specimens were polished and immersed in 10 mLof citric acid (pH=3.2) for 2 h. The eroded specimens were submitted to mechanic brushing according to the 4dentifrices adopted: Colgate Total (control); Colgate Sensitive Pro-Relief; Sensodyne Repair & Protect; or SensodyneRapid Relief. Afterwards, it was conditioned in 37% aqueous phosphoric acid solution. Wettability of 80 specimens(n=10) brushed for 7 or 21 days was evaluated by measuring the contact angle between the dentin surface and adrop of the adhesive Single Bond Universal (3M) with a goniometer. Changes in the surface morphology of 12specimens (n = 3) brushed for 21 days were followed by confocal laser scanning microscopy (CLSM). Data wereanalyzed by two-way ANOVA and Tukey test (p > 0.05). Results: Groups treated with desensitizing dentifricesdid not differ significantly (p < 0.05). Surface treatment and abrasive wear did not interact significantly (p < 0.05).Brushing along 7 days gave the smallest contact angle value (p > 0.05). CLSM images showed morphological changesfor all the groups. Conclusion: The desensitizing dentifrices did not interfere in eroded dentin wettability afterbrushing along 7 or 21 days. Brushing with any of the dentifrices along 21 days promoted open dentinal tubules.KEYWORDSDentifrices; Desensitizing; Toothbrushing; Dentin; Wettability.